Impacts of environmental uncertainty on degree of enterprise financialization and the moderating role of executive incentives - Chen, Dong; Zhu, Yating; Zhou, Na; Xing, Mu (Frontiers in Environmental Science, 2023)
This study takes the panel data of China’s A-share listed companies from 2016 to 2020 as the sample to empirically analyze the impact of Environmental Uncertainty on the degree of corporate financialization, and the moderating role of executive incentive in affecting the relationship between Environmental Uncertainty and the degree of corporate financialization. It is found that the rise of Environmental Uncertainty aggravates the degree of enterprise financialization. Executive equity incentives alleviate the degree of corporate financialization and significantly hedge the effect of Environmental Uncertainty on the degree of corporate financialization. In contrast, executive compensation incentives exacerbate the degree of corporate financialization and do not observably hedge the effect of Environmental Uncertainty on the degree of corporate financialization. Subgroup regressions indicate that the moderating effect of equity incentives on the relationship between Environmental Uncertainty and corporate financialization mainly occurs in non-state-owned firms. The findings of this study provide a theoretical base for firms to develop reasonable and practical incentive mechanisms to cope with environmental uncertainty.